2018
DOI: 10.1111/jeb.13404
|View full text |Cite
|
Sign up to set email alerts
|

Moderate heritability and low evolvability of sperm morphology in a species with high risk of sperm competition, the collared flycatcher Ficedula albicollis

Abstract: Spermatozoa represent the morphologically most diverse type of animal cells and show remarkable variation in size across and also within species. To understand the evolution of this diversity, it is important to reveal to what degree this variation is genetic or environmental in origin and whether this depends on species’ life histories. Here we applied quantitative genetic methods to a pedigreed multigenerational data set of the collared flycatcher Ficedula albicollis, a passerine bird with high levels of ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 84 publications
1
26
0
Order By: Relevance
“…Furthermore, repeated samples across years of the same individuals show high repeatability in total sperm length, suggesting that between-season changes in sperm morphology within an individual are limited [23,31,42,45,46]. Small within-season changes in morphology, in contrast, appear to be relatively common, occurring in most of the species studied [31,42,43,46] (but see [45]). Older male black-throated blue warblers are more likely to obtain and defend territories with high quality nesting and foraging habitat [47], suggesting that, if they therefore have higher body condition (not assessed in this study), body condition could mediate the greater sperm length observed in older birds.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, repeated samples across years of the same individuals show high repeatability in total sperm length, suggesting that between-season changes in sperm morphology within an individual are limited [23,31,42,45,46]. Small within-season changes in morphology, in contrast, appear to be relatively common, occurring in most of the species studied [31,42,43,46] (but see [45]). Older male black-throated blue warblers are more likely to obtain and defend territories with high quality nesting and foraging habitat [47], suggesting that, if they therefore have higher body condition (not assessed in this study), body condition could mediate the greater sperm length observed in older birds.…”
Section: Discussionmentioning
confidence: 95%
“…In the other passerine birds that have been tested, sperm morphology does not differ between young and old males [40][41][42][43][44]. Furthermore, repeated samples across years of the same individuals show high repeatability in total sperm length, suggesting that between-season changes in sperm morphology within an individual are limited [23,31,42,45,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sperm measures vary across the breeding season in some species [64][65][66][67][68] but not all (e.g., [53]). However, our sampling scheme did not allow us to assess or control for such effects here.…”
Section: Statistical Analysis On Spermmentioning
confidence: 99%
“…While there is a growing body of evidence indicating taxonomically widespread phenotypic plasticity in sperm morphology (e.g. [22][23][24]), relatively few studies have addressed plasticity in sperm behaviour. In fish, for example, males were found to produce slower sperm when experimentally promoted to higher ranks in social dominance hierarchies [25] or males responded to perceived sperm competition intensity by producing longer lived [26] or faster sperm [27].…”
Section: Introductionmentioning
confidence: 99%